Variabilité temporelle, diversité et biogéographie des ciliés et dinoflagellés dans l'Océan Arctique - Onda, Deo Florence (Université Laval, 2017)
Impacts of climate change on microbial communities in the Arctic Ocean have been mostly reported for major phytoplankton groups, with less attention to microzooplankton, such as ciliates and dinoflagellates, which have multiple ecological roles. For example, many ciliates and dinoflagellates are mixotrophic and could indirectly influence biogeochemical cycles by grazing on bacterivores and small plankton and linking the microbial loop with the higher trophic levels. The aim of this thesis was to address knowledge gaps in microzooplankton phylogeny, ecology and distribution with a goal of providing information needed to eventually predict of microzooplankton responses to the changing Arctic. We used high throughput amplicon sequencing of the 18S rRNA gene and 18S rRNA (as cDNA) to generate community and diversity profiles, which were used to test hypotheses on microzooplankton assembly across time and space. Results showed that microzooplankton exhibited strong seasonality in response to changing conditions in Amundsen Gulf. Similar summer assemblages were seen from 2003-2010 with the exception in July 2008 following the summer ice minimum record in 2007. Canada Basin dinoflagellate communities were governed by both deterministic and stochastic processes that were dependent on the variability of the environment, indicating potential sensitivity to environmental change. We inferred that dinoflagellates and other taxa with similar functional roles could provide stability to food and energy flows under conditions of light- or nutrient-limitation associated with a deepening nitracline. The high diversity and ubiquity of ciliates and dinoflagellates also suggest a complexity within microbial food webs and new research opportunities for oceanographers. Des impacts du changement climatique sur les communautés de phytoplancton microbien ont déjà été reportés dans l'océan Arctique. Cependant, peu d’attention a été portée sur le microzooplancton aux rôles écologiques multiples tels que les ciliés et les dinoflagellés. Le ...